G(×)=(3×+12)/4
Find g^-1(×)
g^-1(6)
1 answer:
Answer:
fog)(x)=f(g(x))=2(3x+2)−1=6x+4−1=6x+3=3(2x+1)
f
(
x
)
=
3
−
2
x
,
g
(
x
)
=
3
x
2
+
2
Set up the composite result function.
g
(
f
(
x
)
)
Evaluate
g
(
f
(
x
)
)
by substituting in the value of
f
into
g
.
g
(
3
−
2
x
)
=
3
(
3
−
2
x
)
2
+
2
You might be interested in
Answer:
5/20
Step-by-step explanation:
4 people are collecting
1548 /4
387 lbs
Earlier snow depth = 2 feet
later snow depth = 1.6 feet
change
2 - 1.6
0.4 feet
percentage change
(0.4 / 2) * 100
20 %
Answer:
R.I.P Gl man im lost...
Bein aetwo s 26819 andy’s a skid slush’s shell tan 332